A theory of a theory of the smartphone. (September 2021) - Miller, Daniel
This article addresses the consequences of theory in social science. It suggests that theory has become fetishized and contributes to class differentiation as most people are excluded from its increasingly obfuscating form. Fetishism implies that what used to be a means for clarifying and explaining the world has become an end in itself. This article presents an alternative approach to theory as de-fetishized, using as an example a recent attempt to theorize the smartphone. In this approach the processes of abstraction, generalization and de-contextualization that are required to create theory are negated through simultaneous illustration, re-contextualization and forms of highly accessible dissemination. Two examples are provided from our recent theorization of the smartphone, first as the Transportal Home and, second, as Beyond Anthropomorphism.